Does a spouse's health shock influence the partner's risk attitudes? - Johanna Kokot (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
The purpose of this study is to investigate the effect of a spouse's health shock on own risk attitudes. A spouse's health shock (i.e., the occurrence of a severe disease) can influence own expectations about the probability of falling ill. Moreover, an indisposition of the spouse, which may disrupt the ability and efficiency in sharing the everyday responsibilities, can increase mental and financial pressure, and thus would lead to a reduction of own risk willingness. On the other hand, a health shock may act as a wake-up call to enjoy life and may increase risk willingness. Using German Socio Economic Panel data, this study reveals that a health shock suffered by the spouse decreases own risk willingness. The effect is more pronounced the more serious the health shock is. The findings have implications for health insurance decisions and policy evaluations. – – Die vorliegende Studie untersucht den Einfluss eines Gesundheitsschocks des Lebenspartners auf das eigene Risikoverhalten. Ein Gesundheitsschock des Lebenspartners (z.B. eine schwere Erkrankung) kann bewirken, dass sich die eigenen Erwartungen hinsichtlich der Wahrscheinlichkeit selbst zu erkranken, verändern. Darüber hinaus kann eine Erkrankung des Partners das alltägliche Leben so verändern, dass finanzieller und mentaler Druck entsteht, der zu einer Verminderung der eigenen Risikobereitschaft führt. Andererseits kann ein Gesundheitsschock auch als Weckruf wirken, das verbleibende Leben zu genießen, was mit einer erhöhten Risikobereitschaft einhergehen kann. Mit Hilfe von Daten des Sozio-oekonomischen Panels kann in dieser Studie gezeigt werden, dass ein Gesundheitsschock des Partners die eigene Bereitschaft Risiken einzugehen, vermindert. Dieser Effekt ist besonders bei schwerwiegenden Erkrankungen zu beobachten. Die Ergebnisse haben Implikationen für Krankenversicherungsentscheidungen und Politikmaßnahmen.
Keywords: C81; D01; D19; D81; I10; I12; 330; health shock; risk attitudes; spouses